2016
DOI: 10.18343/jipi.21.2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Phytoplankton Communities in Lake Toba, North Sumatera

Abstract: ABSTRAKDanau Toba merupakan danau terbesar di Indonesia yang terletak di Provinsi Sumatera Utara. Danau Toba banyak dimanfaatkan oleh masyarakat untuk kegiatan budi daya ikan di keramba jaring apung (KJA), pertanian, pariwisata, dan pemukiman penduduk. Aktivitas-aktivitas tersebut akan memberikan masukan berupa bahan organik dan anorganik yang akan memengaruhi kualitas air dan dapat menyebabkan terjadinya eutrofikasi. Beberapa indikator eutrofikasi adalah terjadi peningkatan biomassa fitoplankton dan perubahan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
11
0
3
Order By: Relevance
“…At a depth of 0 m, Cyanophyceae was the dominant (54.1%), and Chlorophyceae was least dominant (4.1%). Rahman et al (2016) also observed that Cyanophyceae was mostly found (>40%) in Toba Lake. Meanwhile, Bacillariophyceae was dominant (56.6%) in a 5 m depth, while Chlorophyceae was the least observed (6.3%).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…At a depth of 0 m, Cyanophyceae was the dominant (54.1%), and Chlorophyceae was least dominant (4.1%). Rahman et al (2016) also observed that Cyanophyceae was mostly found (>40%) in Toba Lake. Meanwhile, Bacillariophyceae was dominant (56.6%) in a 5 m depth, while Chlorophyceae was the least observed (6.3%).…”
Section: Resultsmentioning
confidence: 69%
“…The composition of phytoplankton species The results of our study found 12 genera of phytoplankton, i.e., Bacillariophyceae (6 genera), Chlorophyceae (4 genera), and Cyanophyceae (2 genera) in Laguna Lake. The number of genera found in Laguna Lake was less than those of Zhao et al (2016) in Bange Lake who recorded 41 genera, Ganai and Parveen (2014) in Wular Lake who found 64 genera, Rudiyanti et al (2017) in Jatibarang Reservoir who found 21 genera, and Rahman et al (2016) in Toba Lake who recorded 35 genera. Among our finding, Bacillariophyceae was the dominant class in all periods of time and depths, followed by Chlorophyceae.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Various plankton studies have been carried out in lake waters, both natural and artificial lakes, such as Lake Pondok Lapan (Muhtadi et al 2015), Lake Toba (Rahman et al 2016), Lake Ebony (Pratiwi et al 2018a), Lake Matano (Sulawesty 2019), Lake Maninjau (Sulastri et al 2019). Some research on estuarine and mangrove waters has been widely carried out and reported, such as the Mahakam Delta, East Kalimantan (Effendi et al 2016), Belawan Estuary (Dimenta et al 2018), Segara Anakan, Central Java (Dewi et al 2019;Wiyarsih et al 2019); including bay and coastal waters, such as in Gorontalo Bay (Kadim et al 2018), Sunda Strait (Takarina et al 2019), Banten Bay, Lampung and Jakarta (Sidabutar et al 2016;Damar et al 2020).…”
Section: Introductionmentioning
confidence: 99%